Analisis Efektivitas Layanan M-Paspor Berdasarkan ITIL V3 pada Kantor Imigrasi Kelas I TPI Cirebon - Putri Ajeng Larasmanah; Marsani Asfi; Agus (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
This study evaluates the effectiveness of M-Passport service management at the Immigration Office Class I TPI Cirebon using the ITIL V3 framework, focusing on Service Strategy and Service Operation. A quantitative approach was applied through observation, structured interviews, and questionnaires distributed to applicants and staff. Data were analyzed using Maturity Level assessment and GAP Analysis. The findings indicate that the M-Passport service has reached Level 4 (Managed) with an average score of 3.77, showing that processes are measurable, controlled, and consistently implemented. However, Incident Management remains at Level 3 (Defined) with the largest deviation from the expected level, while Problem Management, Request Fulfillment, and Business Relationship Management also show minor gaps. The study recommends strengthening incident handling procedures, enhancing communication strategies, improving applicants’ digital literacy, and increasing staff competencies. These improvements are expected to optimize ITIL V3 implementation and enhance technology-based public service delivery.